PENGARUH GOOD CORPORATE GOVERNANCE, FINANCIAL DISTRESS, DAN LIKUIDITAS TERHADAP KUALITAS LABA - Aprilianus Wanrizky Tita; Hotman Tohir Pohan (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This research was conducted to analyze the effect of good corporate governance, financial distress, and liquidity on earnings quality. The data usedin this study is secondary data obtained from financial statements manufacturing companies listedon the Indonesia Stock Exchange (IDX) for the 2016-2020 period. In this study, earnings quality is measured by discretionary accruals using the Modified Jones Model. From the data collection process, obtained final sample used will be in research asmuch as 305 sample. The research model used in this study is analysis regression multiple linear. The results of this study indicate that the variable proportion of the Independent Board of Commissioners, of the Audit Committee, financial distress, and liquidity take effect on earnings quality. Keywords: The proportion of independent commissioners, of the audit committee, financial distress, liquidity, earnings quality